2007
DOI: 10.1093/intimm/dxl141
|View full text |Cite
|
Sign up to set email alerts
|

CD2 and TCR synergize for the activation of phospholipase C 1/calcium pathway at the immunological synapse

Abstract: Upon conjugation with cognate antigen-presenting cells (APCs), T lymphocytes undergo a sustained [Ca(2+)](i) increase resulting from the engagement of TCR and of accessory molecules with ligands expressed on the surface of APCs. We investigated the contribution of the accessory molecule CD2 to the activation of phospholipase Cgamma1 (PLCgamma1)/calcium pathway in antigen-stimulated T cells. We show that CD2 binding with its ligand CD58 expressed on the surface of APCs augments and sustains antigen-induced [Ca(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…DAG, which serves to recruit RasGRP1, and the DAG metabolizing enzyme DGKa reside at the PM and DAG further accumulates at the IS upon conjugation with APCs (15,35,36). Finally, active PLCg (as evaluated by phosphorylation of Tyr783) specifically and exclusively localizes to the IS of activated T cells (16). All these findings strongly indicate that TCR-induced Ras activation, at least as mediated by the PLCg/ DAG/RasGRP1 pathway, is bound to proceed at the PM of activated T cells and, specifically, at the IS of T cells challenged with APCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DAG, which serves to recruit RasGRP1, and the DAG metabolizing enzyme DGKa reside at the PM and DAG further accumulates at the IS upon conjugation with APCs (15,35,36). Finally, active PLCg (as evaluated by phosphorylation of Tyr783) specifically and exclusively localizes to the IS of activated T cells (16). All these findings strongly indicate that TCR-induced Ras activation, at least as mediated by the PLCg/ DAG/RasGRP1 pathway, is bound to proceed at the PM of activated T cells and, specifically, at the IS of T cells challenged with APCs.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support a model by which Ras activation at different subcellular locations enables T cells to diversify the signaling output of the TCR. In contrast, active PLCg and DAG, both essential upstream activators of RasGRP1, localize exclusively to the PM of activated T cells (15,16), arguing against RasGRP1-dependent Ras activation in endomembranes. Another aspect important to consider is that all reported Ras-GTP imaging data have been recorded in T cells engineered to overexpress Ras.…”
mentioning
confidence: 94%
“…For PLC-γ1 this has been reported for receptors including GPCRs such as the angiotensin II and bradykinin receptors, cytokine receptors and immunoreceptors such as the T cell receptor (92)(93)(94)(95). PLC-γ2 is activated downstream of immunoglobulin and adhesion receptors on immune cells such as B cells, platelets and mast cells (96)(97)(98).…”
Section: Plc-γ Isozymesmentioning
confidence: 92%
“…Role of CD2 on NK cells was much less appreciated although it is a well known co-stimulatory receptor in T cells (30,31). CD2 was abundantly expressed in human T cells and shown to enhance antigen-presenting cell-T cell adhesion and promote T cell activation at lower antigen concentrations (32).…”
Section: Discussionmentioning
confidence: 99%
“…More recent results demonstrated that CD2 ligation with CD58-stimulated T cell signaling cascades involved Lck, TCR chain, and LAT through actin-dependent recruitment to the plasma membrane microdomain (35). Furthermore, CD2 interaction with CD58 on antigen-presenting cells activated PLC-␥ and augmented intracellular calcium release in antigen-specific T cell clones (31). It was also shown that simulation of CD2 up-regulated IL-8 production in human intestinal intraepithelial lymphocytes upon contact with epithelial cells (36).…”
Section: Discussionmentioning
confidence: 99%